Sustainable Financing of Urban Transformation Projects in Environments with High Market Uncertainty: The Case of Türkiye - Gürkan Işık (International Journal of Pioneering Technology and Engineering, 2022)
In the last decade, urban transformation (UT) activities have slowed down considerably in Türkiye due to the financial problems of construction companies originating from the market uncertainties. When large projects in Türkiye are examined closely, it is seen that the financing methods used have also an impact on the failure to ensure financial sustainability and the inability to resist environmental conditions. In this study, financing methods that are currently used, and have the potential to be used are examined and classified in terms of inclusion, and environmental sensitivity. Financing methods are classified according to their dominant characteristics, each class is examined, and compared in terms of its potential about financial sustainability under high uncertainties. Suggestions have also been developed to speed up the UT in the countries having high market uncertainty like Türkiye.